A STUDY ON DIFFICULTIES FACED BY COIR WORKERS IN ALAPPUZHA DISTRICT - Sivaprasad, Akkshay; Das, Sreepriya; S, Sreeram; S, Venugopal (International Journal of Psychosocial Rehabilitation, 2020)
Coir industry in India originated in Kerala which holds the major cottage trade in Kerala and this is recognised as the home of the coir enterprise within India. The workforce is facing several problems in the work environment. The primary goal of the research signified to understand the difficulties, solve the problems of genuine coir workers and also examine whether people reach essential needs. The research held in the decided region with a survey of specific questions to obtain data of a primary source towards the direction of the researcher.The sampling was done to recognise the obstacles regarding coir workers. Each interview was through the schedule.